Terrain Selection by Reindeer in Late Winter in Central Norway - Nellemann, Christian (ARCTIC, 1996)
Characteristics of topography, snow, lichen cover, and lichen distribution were compared with habitat use by Snohetta reindeer (Rangifer tarandus tarandus L.) in central Norway to investigate the role of terrain structure for habitat use within different lichen heath communities. In late winter, density of groups of feeding craters was correlated to indices of terrain ruggedness (TRI) measured at a mesoscale (10-20 m relief), but not to terrain ruggedness measured at a macroscale (30-110 m relief). The use of lichen heaths in rugged terrain (TRI>2.0) was higher than that expected from availability. In rugged terrain, 60-80% of the lichen heaths had less than 40 cm of snow, compared to only 10-30% of the lichen heaths in less rugged areas (TRI<2.0). Rugged terrain types accounted for only 23% of the lichen heath in the study area, and less than 9% of the total area. Available habitat was thus considerably less than that suggested by overall availability of alpine lichen heath. In late winter, ram-hardness of snow exceeded 40 kg, and reindeer cratered mainly where snow was less than 20 cm deep. Reindeer selected narrow (15-25 m broad) and sparsely vegetated ridges with high microtopographic diversity beyond that suggested from availability. Other ridge types with lichen heath were used less than expected from availability. Terrain ruggedness indices may have the potential for estimating the proportion of lichen heath communities that are available in late winter when snow conditions limit availability of forage. On a comparé des caractéristiques relatives à la topographie, à la neige, à la couverture de lichen ainsi qu'à sa répartition avec l'utilisation de l'habitat par le renne Snøhetta (Rangifer tarandus tarandus L.) dans le centre de la Norvège pour savoir quel rôle joue la structure du terrain dans l'utilisation de l'habitat au sein de diverses communautés de bruyère lichénique. À la fin de l'hiver, la densité des regroupements de fosses de broutage a été corrélée avec les indices d'accidents de ...